Implementasi Nilai-Nilai Kitab Nas?ih Al-‘Ib?d Dalam Pembentukan Akhlak Siswa di MA Amanatul Qur’an Pacet Mojokerto - Anir Fikri (Pusdikra Publishing, 2022)
The study in this study focused on the focus of the problem on the values ??of moral education contained in the Nas?ih al-Ib?d book by Shekh Nawawi al-Bantani, along with the implementation of the values ??of the Nas?ih al-'Ib?d book in the moral formation of the students of MA Amanatul Qur'an Pacet Mojokerto, East Java. Data collection instruments in this study used observation, interviews, and documentation, while data analysis used data reduction, data display and conclusion drawing. While the validity of the data using triangulation and refensial adequacy. The results of the research show that there are values ??of moral education in the Nas?ih al-'Ib?d Book which can be implemented in MA Pondok Pesantren Amanatul Qur'an, among the values ??of moral education, namely: the value of believing in Allah SWT, the value of the virtue of seeking knowledge and gaining knowledge that is useful, the value of patience, the value of zuhud, the value of dhikr to Allah SWT, the value of being gentle, the value of the virtue of silence, the value of wara' and the value of qana'ah. In implementing the values ??of moral education at the MA Pondok Pesantren Amanatul Qur'an, the Ustad/Teachers always give ta'dib to the Amanatul Qur'an students, Santi is accustomed to always practice the values ??of moral education, to be applied in their daily lives - day. given teaching and understanding of how important it is to have and practice the values ??of moral education, accompanied by strict supervision and regulations at the Amanatul Qur'an Islamic boarding school applying discipline to students. Based on the results of research in the field, the application of moral education values ??to MA students at the Amanatul Qur'an Islamic Boarding School, can run optimally. However, there are still some educational values ??that they cannot apply optimally, because these values ??are very difficult to apply by some students at MA Amanatul Qur'an, the problem is that there are still some students who cannot change their attitudes and character traits.